Optimization of the Underframe of the Sultan Wind Turbine V5 Using the Optimization Topology Method - Farhan Hafizh Ghifari; Erwin Erwin; Slamet Wiyono (Faculty of Engineering, Andi Djemma University, 2022)
Sultan wind turbine is one of the products of the New Renewable Energy Engineering Lab, Faculty of Engineering Untirta which has developed from year to year until now. To keep up with industrial developments in today's era, renewal is needed to improve and update the technology contained in the sultan wind turbine. In particular, today's optimization topologies are seen as providing the possibility to realize truly manufacturing-optimized designs through topology optimization. A topological optimization is an approach that is considered powerful in design because it contributes to designs that can save energy, materials ,and time that cannot be achieved economically using other manufacturing processes. A topological optimization, as it is often called, computer configuration of the best material over 3D space, usually represented as a grid, to satisfy or optimize physical parameters. Designers using these automated systems often seek to understand the interaction of physical constraints with the final design and their implications for other physical characteristics. Such understanding is a challenge to using a visualization approach to explore the design solution space. The essence of our new approach is to summarize an ensemble of solutions by automatically selecting a set of examples and parameterizing a design space.